2005
DOI: 10.1902/jop.2005.76.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin Expression in Human Monocytes: Induction by Porphyromonas gingivalis Lipopolysaccharide, Tumor Necrosis Factor‐α, and Interleukin‐1β

Abstract: These results demonstrate that P-LPS, TNF-alpha, and IL-1beta induce calprotectin production from human monocytes and that this production is associated with the activation of DNA C/EBPalpha binding complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47]. As a result, calprotectin could contribute to the host inflammatory immune defense against bacteria in periodontal disease [8,9,48,49]. In an in vitro study, epithelial calprotectin was shown to promote resistance to Porphyromonas gingivalis invasion and thereby reduce bacterial invasion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47]. As a result, calprotectin could contribute to the host inflammatory immune defense against bacteria in periodontal disease [8,9,48,49]. In an in vitro study, epithelial calprotectin was shown to promote resistance to Porphyromonas gingivalis invasion and thereby reduce bacterial invasion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin level in gingival crevicular fluid (GCF) of periodontitis patients was significanly higher than healthy subjects and it was detected in gingival tissue only from the periodontitis patients. 1,2 It was also known that calprotectin has the extracellular function, including antibacterial, chemotactic factor, and inhibition binding of pathogenic bacteria to the epithelial cell, suggest that calprotectin may play a role in the immune response mechanism of periodontitis 9 . However, the exact role of calprotectin in periodontitis patient with diabetes mellitus is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration also increases compared with healthy patients. 8 In addition, the in vitro study shows that calprotectin has anti-microbe function, bacteriastatics and fungistatics with Minimal Inhibitory Concentration (MIC) that is similar with some antibiotics. The mechanism of this action is actually caused by the increasing of bacteria binding zinc needed for proliferation.…”
mentioning
confidence: 99%
“…The concentration of calprotectin in the gingival crevicular fluids can also reflect the severity of the inflammation in patients with periodontal disease. 7,8 Thus, in order to analyze the mechanism or pathogenesis of this disease, the concentration of calprotectin showing the degree of the inflammation in those patients with aggressive periodontitis must be examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation